2020
DOI: 10.1186/s13717-020-00267-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric CO2 impact on carbon and nitrogen transformations and microbial community in replicated wetland

Abstract: Background Elevated atmospheric CO2 has direct and indirect influences on ecosystem processes. The impact of elevated atmospheric CO2 concentration on carbon and nitrogen transformations, together with the microbial community, was evaluated with water hyacinth (Eichhornia crassipes) in an open-top chamber replicated wetland. The responses of nitrogen and carbon pools in water and wetland soil, and microbial community abundance were studied under ambient CO2 and elevated CO2 (ambient + 200 μL L−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The contamination of water, soil, and air by oil and gas wastes as well as its associated byproducts is a possibility. Reports by citizens have shown the relative effect of production and drilling activities on the contamination of surface waters, soils surrounding well sites, and water wells; air emissions emanating from wellheads, pipelines, drilling sites, compressor stations, and several other oil and gas field infrastructure have been reported to pose air quality concerns (Jiang et al 2020 ). Other significant environmental threats are those emanating from the dust particles left from drilling which can coat the surrounding areas, as well as flames produced upon combustion of natural gas in the oil fields which are known to cause air pollution.…”
Section: Environmental Pollution As a Results Of Crude Oil Exploration And Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The contamination of water, soil, and air by oil and gas wastes as well as its associated byproducts is a possibility. Reports by citizens have shown the relative effect of production and drilling activities on the contamination of surface waters, soils surrounding well sites, and water wells; air emissions emanating from wellheads, pipelines, drilling sites, compressor stations, and several other oil and gas field infrastructure have been reported to pose air quality concerns (Jiang et al 2020 ). Other significant environmental threats are those emanating from the dust particles left from drilling which can coat the surrounding areas, as well as flames produced upon combustion of natural gas in the oil fields which are known to cause air pollution.…”
Section: Environmental Pollution As a Results Of Crude Oil Exploration And Processingmentioning
confidence: 99%
“…Several activities in crude oil processing ranging from extraction, refining, transportation, and gas flaring introduce greenhouse gases especially carbon dioxide into the atmosphere. The process of burning fossil fuels (coal), oil, and gas leading to the emission of carbon dioxide (a greenhouse gas) has led to global warming raising serious environmental challenges (Darkwah et al 2018 ; Jiang et al 2020 ). Also, the flaring of gases rich in a liquid produces smoke having aerosols that also contribute to global warming (FOE 2004 ; Darkwah et al 2018 ).…”
Section: Environmental Pollution As a Results Of Crude Oil Exploration And Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample relationship (R 2 ) was statistically evaluated by the linear regression analysis of SPSS Statistics 17.0 (SPSS Inc., USA). All chemical analysis determinations for sediment samples were performed in a triplicate form (Huang et al 2019;Jiang et al 2020;Norgbey et al 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…While carbon accrual into the soil from increased plant productivity is beneficial, climate change effects such as elevated atmospheric carbon dioxide and temperatures can also disrupt the carbon cycle by modifying the rate of carbon loss to the atmosphere (Borer et al 2017, Lange et al 2015). Previous studies have shown that high levels of carbon dioxide in the atmosphere increase plant growth leading to higher amounts of respired carbon from microbial decomposition (Jiang et al 2020). Increased temperatures also promote higher rates of decomposition (Cavicchioli et al 2019).…”
Section: Introductionmentioning
confidence: 99%